2021
DOI: 10.1007/s40279-021-01445-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Acclimation and Acclimatisation on Maximal Aerobic Capacity Compared to Exercise Alone in Both Thermoneutral and Hot Environments: A Meta-Analysis and Meta-Regression

Abstract: Background Heat acclimation and acclimatisation (HA) is typically used to enhance tolerance to the heat, thereby improving performance. HA might also confer a positive adaptation to maximal oxygen consumption ($$V{\text{O}}_{2\max }$$ V O 2 max ), although this has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…Together, these aspects points to the limited statistical power of the present study to detect changes in cardio‐respiratory parameters and subsequent performance. The observed lack of statistical effects of heat training on V̇O 2max despite an increase in Hb mass is in agreement with previous studies investigating the effects of prolonged heat training, 6,34 though a recent meta‐analysis revealed that 5–60 days of heat training can enhance V̇O 2max in thermoneutral environments by a magnitude likely missed in small scale studies 35 . Furthermore, there were no differences between the groups in any of the other investigated physiological determinants of endurance performance such as work economy, fractional utilization of V̇O 2max , running velocity associated with 4 mmol·L −1 [La − ], or time to exhaustion during the graded V̇O 2max test to exhaustion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Together, these aspects points to the limited statistical power of the present study to detect changes in cardio‐respiratory parameters and subsequent performance. The observed lack of statistical effects of heat training on V̇O 2max despite an increase in Hb mass is in agreement with previous studies investigating the effects of prolonged heat training, 6,34 though a recent meta‐analysis revealed that 5–60 days of heat training can enhance V̇O 2max in thermoneutral environments by a magnitude likely missed in small scale studies 35 . Furthermore, there were no differences between the groups in any of the other investigated physiological determinants of endurance performance such as work economy, fractional utilization of V̇O 2max , running velocity associated with 4 mmol·L −1 [La − ], or time to exhaustion during the graded V̇O 2max test to exhaustion.…”
Section: Discussionsupporting
confidence: 91%
“…The observed lack of statistical effects of heat training on VȮ 2max despite an increase in Hb mass is in agreement with previous studies investigating the effects of prolonged heat training, 6,34 though a recent meta-analysis revealed that 5-60 days of heat training can enhance VȮ 2max in thermoneutral environments by a magnitude likely missed in small scale studies. 35 Furthermore, there were no differences between the groups in any of the other investigated physiological determinants of endurance performance such as work economy, fractional utilization of VȮ 2max , running velocity associated with 4 mmol•L −1 [La − ], or time to exhaustion during the graded VȮ 2max test to exhaustion. The present findings are partly in agreement with previous 5 weeks heat training studies where a 3-4.5% increase in Hb mass failed to induce a significant performance increase.…”
Section: Heat Suit Training and Blood Variablesmentioning
confidence: 94%
“…This may seem surprising, as there is a strong relationship between total Hb mass and V̇O 2max , with each g increase in hemoglobin having been proposed to lead to 4 mL·min −1 increases in V̇O 2max (31). Regardless of this, the observed lack of statistical effects of heat training on V̇O 2max despite an increase in Hb mass is in agreement with previous studies investigating the effects of prolonged heat training (4,8), although a recent meta-analysis revealed that heat training can enhance V̇O 2max in thermoneutral environments by a small, but significant amount (32). Furthermore, V̇O 2max is influenced by factors other than Hb mass (1).…”
Section: Discussionsupporting
confidence: 91%
“…The present findings suggest that short-term HA training under hot conditions does not affect iron metabolism, at least in terms of hepcidin activity. Therefore, endurance training under hot conditions can improve thermoregulatory capacity and endurance capacity (Lorenzo et al 2010 ; Tyler et al 2016 ; Saunders et al 2019 ; Waldron et al 2021 ) without affecting iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of HA on exercise-induced hepcidin elevations remains unclear. Endurance training under hot conditions (i.e., HA training) is a well-established method to improve thermoregulatory capacity and endurance performance (Lorenzo et al 2010 ; Tyler et al 2016 ; Saunders et al 2019 ; Waldron et al 2021 ), and is widely accepted as a useful form of training among various types of endurance athletes. A better understanding of hepcidin activity in association with iron metabolism is important, as endurance athletes commonly incorporate several days of endurance training under hot conditions into their training schedule (i.e., training camps).…”
Section: Introductionmentioning
confidence: 99%